Analisis Pengendalian Persediaan Bahan Baku Dengan Menggunakan Metode Material Requirement Planning pada Toko Roti Primadonna Solo - Dwi Astuti, Alfiana; Widajanti, Erni (Teewan Journal Solutions, 2025)
Toko Roti Primadonna Solo is one of the companies that not only produces wet bread, but also produces various breads and pastries. The availability of sufficient raw materials is an important factor to ensure the smooth production process. Therefore, running a smooth production process requires a good production system. The purpose of this study is to analyse the cost efficiency of wheat flour raw material inventory using the Material Requirement Planning (MRP) method, which consists of the Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ) methods. The results showed that the total cost of raw material inventory according to the policy of Primadonna Solo Bakery of Rp 1,132,000 is greater than the calculation using the MRP method. The total cost of raw material inventory with the Lot For Lot (LFL) method is Rp 204,000, EOQ is Rp 548,500 and with the POQ method is Rp 204,000. From the calculation of the total cost of raw material inventory, the MRP method can streamline the cost of raw material inventory, especially the LFL and POQ methods